Simulations for Optimization of Proton Dose Delivery using the Advanced Markus Chamber - Kalamara, Antigoni; Stamatelatos, I. E.; Stefanopoulos, K. L.; Theodossiou, T. A. (HNPS Advances in Nuclear Physics, 2026)
The Advanced Markus chamber is a vented, plane-parallel ionization chamber widely used in proton dosimetry, particularly in cases involving narrow spread-out Bragg peaks or steep depth-dose gradients. As part of the NuCapCure project, a series of in vitro and animal model irradiation experiments will be conducted to evaluate the efficacy of novel radiosensitive compounds designed to enhance the cancer cell-killing potential of proton therapy. To support these experiments, Monte Carlo simulations were carried out using the MCNP 6.1 code to model the irradiation setup at the Oslo Cyclotron Laboratory (OCL) that employs the MC-35 Scanditronix AB cyclotron. The computational model included the 16 MeV proton source, a tungsten filter, a beam monitor, and the Advanced Markus chamber. Special attention was paid to the effect of the chamber’s entrance window, as it influences the location of the proton Bragg peak. The results of this study allow the optimal positioning of both the Markus chamber and the biological samples, thereby maximizing dose delivery during proton irradiation experiments.